Jinadatta Suri is depicted here with his disciple - Temples of India Project Team (Jio Institute, 2024)
Jinadatta Suri is depicted here with his disciple, who is curing a person of his ailment. The acharya (those who impart knowledge) is renowned for such miraculous deeds. This seventh oval painting (in clockwise order) in the lower/outer circle in the ceiling of the mandapa (pillared hall) is the last of four paintings dedicated to the miracles of Jinadatta Suri, through which the acharya saved several lives. The inscription reads, ‘Shri Jinadatta Suriji sapata spa dene ji vayo.’